2017
DOI: 10.1073/pnas.1712453115
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signaling through Drosophila Mthl10 ties lifespan to environmental stress

Abstract: A systems-level understanding of cytokine-mediated, intertissue signaling is one of the keys to developing fundamental insight into the links between aging and inflammation. Here, we employed , a routine model for analysis of cytokine signaling pathways in higher animals, to identify a receptor for the growth-blocking peptide (GBP) cytokine. Having previously established that the phospholipase C/Ca signaling pathway mediates innate immune responses to GBP, we conducted a dsRNA library screen for genes that mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…In addition, we identify new potential markers: Metallothionein A (MtnA), Malic enzyme (Men), and CG9119. Further analysis of the GO terms highlights the response to starvation (Lipin (Lpin), Mthl10) as well as enzymes essential for the biosynthesis of proteoglycans (Sugarless, sgl) and glucose homeostasis (Pfk, 6‐phosphofructo‐2‐kinase (pfrx), and Aldolase (ald); Hacker et al , ; Flowers et al , ; Ugrankar et al , ; Dudzic et al , ; Enzo et al , ; Sung et al , ; Wong et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we identify new potential markers: Metallothionein A (MtnA), Malic enzyme (Men), and CG9119. Further analysis of the GO terms highlights the response to starvation (Lipin (Lpin), Mthl10) as well as enzymes essential for the biosynthesis of proteoglycans (Sugarless, sgl) and glucose homeostasis (Pfk, 6‐phosphofructo‐2‐kinase (pfrx), and Aldolase (ald); Hacker et al , ; Flowers et al , ; Ugrankar et al , ; Dudzic et al , ; Enzo et al , ; Sung et al , ; Wong et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we identify new potential markers: Metallothionein A (MtnA), Malic enzyme (Men) and CG9119. Further analysis of the GO terms highlights the response to starvation (Lipin (Lpin), Mthl10) as well as enzymes essential for the biosynthesis of proteoglycans (Sugarless, sgl) and glucose homeostasis (Pfk, 6-phosphofructo-2-kinase (pfrx), Aldolase (ald)) (Dudzic et al, 2015; Enzo et al, 2015; Flowers et al, 2007; Hacker et al, 1997; Sung et al, 2017; Ugrankar et al, 2011; Wong et al, 2019). This suggests that the CC do not operate with the same metabolic pathway as the majority of the WL hemocytes, for which the bulk RNA seq data indicate a lipid based metabolism ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the mth gene is related to lifespan and stress resistance in D. melanogaster (Lin et al, 1998). D. melanogaster mthl10 is one of the paralogues of mth (Patel et al, 2012;Friedrich and Jones, 2017) which initiates PLC/Ca 2+ signalling to mediate immunological, metabolic and stressprotective responses and lifespan functions in response to the ligand growth-blocking peptide (GBP) (Sung et al, 2017). Recent research has revealed that 16 members of the Mth/Mthl gene family in D. melanogaster consists of both Mth ectodomain-positive and Mth ectodomainnegative members (Friedrich and Jones, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al (2002) reported mth in the presynaptic motor neurone acutely upregulates neurotransmitter exocytosis at the larval neuromuscular junction. D. melanogaster Mthl10 is expressed in the central nervous system and fat bodies (Patel et al, 2012), integrating immunological and stressprotection functions (Sung et al, 2017). Therefore, tissue expression profiles of the LOC101899380 gene reveal it is probably associated with synaptic transmission and stress resistance.…”
Section: Discussionmentioning
confidence: 99%